Derivatives as Hedging tools for Agribusiness – FX (Research, Society and Development, 2022)
Agrobusiness is a branch of activity with a high risk compared to other business activities, including the biological nature of its production. The modern management of this branch of activity emphasizes more and more the predictability of its activities, and the management of risks gains prominence. This context or use of Derivatives spread as a powerful tool for this purpose. The objective of the research is to address the evolution of derivatives, their accounting standards and how the use of these instruments adds value to agribusiness companies. It was used as a case study for the SLC Agrícola company, through its Patrimonial Balance with a focus on neutralizing product risks and volatility in the Cash Flow. The results obtained show the relevance of the protection with Derivatives in predictability in agribusiness. Additionally, the framework of accounting and financial regulations in force, allows Risk Management at various levels of the company, allowing the efficiency of each derivative to be attributed according to its corresponding object and above all, separating its result and exposure from the Company's operational part. It is considered that a company with decades of operation does not make a planned and efficient use of Hedge in the parts that it judges will be the most relevant in its business.